Perancangan Aplikasi Pengolah Data Siswa Berbasis Android: Studi Kasus: SDN 107453 Kampung Jawa Serdang Bedagai - Alda, Muhamad; Putri Ratricia; Atika Sari Br Pa; Arief Fathurrahman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Technology is developing very quickly, especially in the field of information systems. Information technology is essential to every business, organization, government agency, and educational institution for data management and security purposes. As a result, it is critical that businesses, governments, or educational institutions put in place information systems that can be trusted to handle data processing smoothly and to help speed up task completion. A system is a collection or set of elements or variables that are interrelated, interact with each other, and depend on each other to achieve goals. Design is the stage in building a system after the system analysis stage and the system development cycle. In making the system, the tools used in making plans and designs are using Unifield Modeling Language (UML). Unifield Modeling Language is a language that has become the industry standard for visualizing, designing and documenting software systems. Use Case is one of the tools used to model user interactions with the system. Implementation is the application of how the system works based on the results of analysis and designs that have been made previously into a particular programming language.